PENGARUH PEMBERIAN BIOCHAR DARI BEBERAPA BAHAN BAKU DANPUPUK KIESERIT TERHADAP SIFAT KIMIA TANAH DAN PRODUKSI TANAMAN BAWANGMERAH (Allium ascalonicum L.) DI LAHAN SAWAH - Tambun Sihotang; Posma Marbun; Abdul Rauf (Jurnal Mantik Penusa, 2018)
This research was conducted toEffects of Biochar from some materials and Kieserit to the Soil Chemical Properties and Shallot Production (Allium ascalonicum L.) in Paddy Fields. This research was conducted at the paddy field of Medan SelayangSubdistrict, which about ± 32 meters above sea level. This research was conducted from May to August 2018. The method used in this research was factorial randomized block design with two factors, i.e: Kieserit (0g /plot, 5g/plot, 10g/plot, 15g/plot) and biochar administration (rice husk biochar 1 kg / plot, 1 kg rice straw biochar/plot, biochar oil palm empty fruit bunch 1 kg/plot). Parameters observed were pH H2O, N-total, C-organic, CECand dry weight bulb of tubers per clump. The results showed that biochar had a significant effect on pH H2O, CEC and dry weight of tubers per hill, but no significant effect on N-total, C-organic and number of tubers per clump. Kieserit fertilizer has no significant effect on all parameters. The interaction between biochar and Kieserit has no significant effect on all parameters. Rice straw biochar is better in improving soil chemical properties and onion production.Keywords: Biochar, Kieserite Fertilizer, Soil Chemical Properties,Shallot